Foreign Workers’ Recruitment and Reconsideration of Crucial Factors: A Sequential Exploratory Mixed-Methods Study of Migrant Labourers in Malaysia - Al Masud, Sheikh Mohammad Maniruzzaman; Rohana, Hamzah; Hasan, Ahmad (Transnational Press London, 2022)
Malaysia has witnessed an influx of foreign workers, mainly due to its rapidly expanding economy. However, low-skilled or uneducated migrants prevail in the labour market, which places immense pressure on the Malaysian economy. This study aimed to identify some crucial factors related to foreign workers requiring reconsideration at the recruitment phase. It was a sequential exploratory mixed-method study. Data were collected using qualitative (in-depth interviews) and quantitative (face-to-face surveys) methods. The study found that some recruitment factors should be reassessed, such as fixing the minimum educational qualification at the recruitment level, mandatory skill tests and compulsory pre-departure training for selected workers. The findings of this study will help in redesigning foreign worker recruitment policies. Moreover, the results will also assist in guiding the sustainable enhancement of workforce contributions to society and the Malaysian economy.